PENGARUH EMOTIONAL MARKETING DAN PRODUCT PERCEPTION TERHADAP BRAND AWARENESS PEMBELI ONLINE SHOP STUDI MAHASISWA FEBI IAIN KENDARI - Meilani, Tantri; Utomo, Agus Prio (IAIN Kendari, 2023)
This research aims to determine the influence of emotional marketing and product perception on brand awareness of online shop buyers. This research is quantitative research with a survey method. The population in this study were FEBI IAIN Kendari students who often or had shopped at online shops and had seen advertisements/live sales. The sampling technique in this research used a convenience sampling technique with a purposive sampling technique. Data collection was carried out using offline and online questionnaires which had been tested for validity and reliability. Data were analyzed using multiple linear regression test statistics, including the t test, f test and coefficient of determination (R2) to answer the hypothesis. The results of this analysis show that; (1) there is a positive and significant influence between emotional marketing and brand awareness, as evidenced by the calculated t value of 3.320 which is greater than the t table value of 1.985; (2) there is a positive and significant influence between product perception and brand awareness, as evidenced by the t table value of 6.788 which is greater than the t table value of 1.985 Penelitian ini bertujuan untuk mengetahui pengaruh emotional marketing dan product perception terhadap brand awareness pembeli online shop. Penelitian ini merupakan penelitian kuantitatif dengan metode survey. Populasi pada penelitian ini mahasiswa FEBI IAIN Kendari yang sering atau pernah berbelanja di online shop dan telah melihat iklan/live penjualan. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik convienence sampling dengan teknik purposive sampling. Pengumpulan data dilakukan dengan menggunakan kuesioner offline dan online yang telah diuji validitas dan reliabilitasnya. Data dianalisis dengan statistik uji regresi linier berganda, diantaranya uji t, uji f dan koefisien determinasi (R2) untuk menjawab hipotesis. Hasil analisis ini menunjukkan bahwa; (1) terdapat pengaruh positif dan signifikan antara emotional marketing terhadap brand awareness, dibuktikan nilai t hitung sebesar 3,320 lebih besar dari nilai t tabel 1,985; (2) terdapat pengaruh positif dan signifikan antara product perception terhadap brand awareness, dibuktikan dari nilai t tabel 6,788 lebih besar dari nilai t tabel 1,985. A B S T R A C TThis research aims to determine the influence of emotional marketing and product perception on brand awareness of online shop buyers. This research is quantitative research with a survey method. The population in this study were FEBI IAIN Kendari students who often or had shopped at online shops and had seen advertisements/live sales. The sampling technique in this research used a convenience sampling technique with a purposive sampling technique. Data collection was carried out using offline and online questionnaires which had been tested for validity and reliability. Data were analyzed using multiple linear regression test statistics, including the t test, f test and coefficient of determination (R2) to answer the hypothesis. The results of this analysis show that; (1) there is a positive and significant influence between emotional marketing and brand awareness, as evidenced by the calculated t value of 3.320 which is greater than the t table value of 1.985; (2) there is a positive and significant influence between product perception and brand awareness, as evidenced by the t table value of 6.788 which is greater than the t table value of 1.985.